Sistematización de la experiencia de diseño, actualización del mejoramiento del manual de perfiles y cargos, en la Empresa Marathon Sports, en el periodo noviembre 2015 a junio del 2016. - Melo Lovato, Karla Mishell (2017)
The objective of this work is the lifting of the responsibilities of the personnel of the company Marathon Sports, allowing to define the duties of each position getting a friendly person to person of the activities that are carried out and the profile that is needed for the position of responsibilities and requirements, identifying the person suitable to be in the same, each head of area approves the positions that Have been raised so as to make known to each person what their place in the organization chart and what their functions are in addition to making known what is needed to fill each position regarding responsibilities, skills, knowledge, studies, language, skills, aptitudes. Applied the method of personal interviews, looking for the company to benefit from the moment in which you have to select a person to occupy any of the positions that exist in the organization. As a result they will hire people to select a person to occupy any of the positions that exist in the organization, hiring people who meet the requirements, knowledge and experience, so that they comply with its functions efficiently And effectively giving optimal results, meeting objectives and integrating into the organizational culture and thus giving a better service to internal and external customers. It is concluded that amount and it is necessary to have an updated profiles manual, clear, functional and understood by each occupant of the post.